Comparative proteome analysis reveals possible heterosis for growth, immunity and antioxidation mechanisms in Macrobrachium nipponense hybrid offspring and parent populations. (27th October 2022) - Li, Yiming; Ye, Yucong; Jiang, Qichen; Che, Xuan; Zhao, Yunlong
Abstract: Macrobrachium nipponense, an important economic aquaculture species in China, is experiencing degradation of shrimp germplasm resources. Hybridization is a means of genetic improvement and can contribute to overcoming this serious problem. However, the molecular mechanisms of heterosis resulting from hybridization is unknown. In this study, LC–MS/MS combined with TMT tags were used for comparative proteomics analyses of the broodstock populations (Dianshan, DS) and hybrid offspring (DS ♀ × CD [Changjiang, CJ ♂ × Dongting, DT ♀], SCD) in M. nipponense . A total of 57 differentially expressed proteins (DEPs) were identified, of which 35 proteins were up‐regulated and 22 proteins were down‐regulated. The results showed that the 57 differential proteins correspond to three functional types, including 431 biological processes, 458 cellular components and 762 molecular functions. KEGG pathway analyses identified growth‐ and immunity‐related pathways, including alanine, aspartate and glutamate metabolism (ko00250), arginine biosynthesis (ko00220), arginine and proline metabolism (ko00330), hippo (ko04390), apoptosis (ko04215), p53 (ko04115) and complement system (ko04610). The expression of genes encoding the differentially expressed proteins were verified using real‐time quantitative PCR, and the results showed that the hybrid population was superior to the parent population in terms of growth and immunity. This study provided important data for genetic and breeding research of Macrobrachium nipponense .